UV-cured polyacrylate pressure-sensitive adhesive and preparation method thereof

By introducing functional monomers and composite flame retardants into UV cured polyacrylate pressure-sensitive adhesive, the problem of insufficient water resistance and flame retardant performance is solved, and high-performance pressure-sensitive adhesive is realized, suitable for automobile and furniture manufacturing. Packaging and other fields.

CN119432272APending Publication Date: 2025-02-14NANXIONG YALTON CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411696064.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing UV cured polyacrylate pressure-sensitive adhesives have insufficient water resistance and flame retardant properties, which limits their application in automobiles, furniture manufacturing, packaging and other fields.

Method used

The water resistance and flame retardant properties of pressure-sensitive adhesives are improved by introducing functional monomers and composite flame retardant. Functional monomers are produced by the reaction of ester-based silicone oil and allylamine, and have excellent water resistance; the composite flame retardant significantly improves the flame retardant performance through the synergistic action of imidazole, elolite nanotubes and amide.

Benefits of technology

It significantly improves the water resistance and flame retardant properties of pressure-sensitive adhesives, meets the high-performance requirements in actual applications, and has good application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of ultraviolet curing pressure-sensitive adhesives, and discloses a UV curing polyacrylate pressure-sensitive adhesive and a preparation method thereof. The polyacrylate pressure-sensitive adhesive prepared by the invention overcomes the defects of poor water resistance, poor flame retardant property and the like of the traditional pressure-sensitive adhesive; due to the introduction of the functional monomer, the water resistance of the pressure-sensitive adhesive can be improved by utilizing organic silicon, and the phenomena of expansion, softening and the like caused by stimulation of factors such as moisture and moisture in an external environment are reduced; according to the composite flame retardant, the flame retardant property of a matrix is improved by adopting an organic and inorganic combined mode. Therefore, the polyacrylate pressure-sensitive adhesive disclosed by the invention has a good application prospect in the fields of automobiles, furniture manufacturing, packaging and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultraviolet curing pressure-sensitive adhesives, and in particular to a UV curing polyacrylate pressure-sensitive adhesive and a preparation method thereof. Background Art

[0002] Pressure-sensitive adhesive is a special adhesive that can bond with the adherend under slight pressure, and the adhesive layer will not dry for a long time. It is mainly used as a material for preparing pressure-sensitive tapes, and is made into pressure-sensitive adhesive products such as tapes, stickers, films, and films. Pressure-sensitive adhesives can be divided into two categories according to the main components: rubber and resin. Resins include polyurethanes, acrylates, silicones, etc. Among them, UV-curing polyacrylate pressure-sensitive adhesive is the most widely used resin pressure-sensitive adhesive. It does not contain solvents and is in a viscous liquid state at high temperatures. It is applied to the substrate when used. Its curing process is mainly achieved through photopolymerization reaction under UV light irradiation. After curing, the performance of the film is stable and it can still maintain good bonding properties after long-term use. Therefore, UV-curing polyacrylate pressure-sensitive adhesive is widely used in the automotive industry, furniture manufacturing, medical equipment, packaging and other fields due to its advantages of high efficiency, energy saving and environmental protection.

[0003] However, as the scope of practical application expands, the performance requirements for UV-curable polyacrylate pressure-sensitive adhesives have also increased. For example, pressure-sensitive adhesives are flammable polymers, and their application in the fields of automobiles, furniture manufacturing, packaging, etc. is greatly limited; in addition, considering the poor water resistance of polyacrylate pressure-sensitive adhesives, the water resistance of pressure-sensitive adhesives needs to be improved. Therefore, it is necessary to improve the flame retardant and water resistance of pressure-sensitive adhesives to meet actual needs. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a UV-curable polyacrylate pressure-sensitive adhesive and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A UV curing polyacrylate pressure-sensitive adhesive comprises the following raw materials in parts by weight: 45-55 parts of isooctyl acrylate, 15-25 parts of butyl acrylate, 8-15 parts of methyl methacrylate, 1-3 parts of acrylic acid, 5-9 parts of functional monomers, 5-10 parts of composite flame retardants, 0.1-0.3 parts of crosslinking agents, and 0.1-2 parts of photoinitiators;

[0007] The photoinitiator is a photoinitiator TPO (trimethylbenzoyl-diphenylphosphine oxide);

[0008] The crosslinking agent is trimethylolpropane triacrylate;

[0009] The functional monomer is prepared by the following steps:

[0010] Step A1, after heating and vacuum dehydrating methyl methacrylate, add chloroplatinic acid isopropanol solution and toluene, replace with nitrogen three times, add hydrogenated silicone oil dropwise under nitrogen, heat to 80-90°C for reaction for 1.5-2.5h, and distill under reduced pressure to obtain esterified silicone oil;

[0011] Step A2, under nitrogen conditions, esterified silicone oil was mixed and stirred evenly in N, N-dimethylformamide, and the temperature was lowered to 0°C, and then allylamine was slowly added and stirred for 10-30 minutes, and then the temperature was raised to 120-140°C for reaction for 2-3 hours, and rotary evaporated to obtain a functional monomer;

[0012] Furthermore, in step A1, the amount ratio of methyl methacrylate, chloroplatinic acid isopropanol solution, toluene and hydrogen-containing silicone oil is 0.2-1g:5-10g:50mL:2-5g, and the chloroplatinic acid isopropanol solution is prepared by mixing chloroplatinic acid and isopropanol in a mass ratio of 0.05-0.1:100;

[0013] Furthermore, in step A2, the usage ratio of esterified silicone oil, N,N-dimethylformamide and allylamine is 1-5g:100mL:0.5-2g.

[0014] The composite flame retardant is prepared by the following steps:

[0015] Step B1, under nitrogen conditions, imidazole was added to methanol and mixed and stirred evenly, and then methyl acrylate was slowly added, and the temperature was raised to 35° C. and stirred for reaction for 3-5 hours to obtain intermediate product 1;

[0016] Step B2, mix cyanuric chloride, sodium hydroxide and acetone evenly, control the temperature at 0-5°C, slowly add allylamine acetone solution, stir and react for 2-3h, then heat to 40-50°C, slowly drop half volume of ethylenediamine acetone solution and half volume of 0.1mol / L sodium hydroxide solution in sequence, stir and react for 2-3h, then heat to 90°C, add the remaining volume of ethylenediamine acetone solution and the remaining volume of 0.1mol / L sodium hydroxide solution, stir and react for 1-2h, and obtain intermediate product 2;

[0017] Step B3, under nitrogen conditions, cool the intermediate product 2 to 0°C, slowly add the intermediate product 1 and stir for 30 minutes, then heat to 130-150°C and react for 2-3 hours to obtain an organic flame retardant;

[0018] Step B4, uniformly dispersing the halloysite nanotubes in 1,4-dioxane, adding KH570 (γ-methacryloxypropyltrimethoxysilane), heating to 80-90° C., stirring and reacting for 4-6 hours, filtering, washing and drying to obtain an inorganic flame retardant;

[0019] Step B5, adding an organic flame retardant and an inorganic flame retardant to N,N-dimethylformamide and stirring to mix evenly, then adding dicumyl peroxide, heating to 45-55° C., stirring to react for 2-3 hours, filtering, washing, and drying to obtain a composite flame retardant;

[0020] Further, in step B1, the usage ratio of imidazole, methanol and methyl acrylate is 0.01-0.03 mol:100 mL:0.01-0.03 mol;

[0021] Further, in step B2, the dosage ratio of cyanuric chloride, sodium hydroxide, acetone, allylamine acetone solution, ethylenediamine acetone solution and sodium hydroxide solution is 0.01-0.02 mol: 0.2-0.4 g: 100 mL: 50 mL: 100 mL: 8-16 mL;

[0022] Furthermore, in step B2, the allylamine acetone solution is prepared by mixing allylamine and acetone in a ratio of 0.01-0.02 mol:50 mL, and the ethylenediamine acetone solution is prepared by mixing ethylenediamine and acetone in a ratio of 0.02-0.04 mol:100 mL;

[0023] Further, the molar ratio of the intermediate product 1 in step B3 to the ethylenediamine in step B2 is 1:1;

[0024] Further, in step B4, the usage ratio of halloysite nanotubes, 1,4-dioxane and KH570 is 1-3 g:50 mL:0.05-0.2 g;

[0025] Furthermore, in step B5, the usage ratio of the organic flame retardant, the inorganic flame retardant, N,N-dimethylformamide and dicumyl peroxide is 0.5-1.5 g: 1-2 g: 100 mL: 0.005-0.015 g.

[0026] A method for preparing a UV-curable polyacrylate pressure-sensitive adhesive comprises the following steps:

[0027] Step S1, weigh the raw materials by weight, mix isooctyl acrylate, butyl acrylate, methyl methacrylate, acrylic acid, functional monomers and part of the photoinitiator, and illuminate the mixture with a low-pressure mercury lamp at 1-5 mW / cm2 under nitrogen conditions. 2 Irradiate with ultraviolet light of intensity of 2-4min to obtain material A;

[0028] Step S2: after the composite flame retardant, the crosslinking agent and the remaining amount of the photoinitiator are uniformly mixed, material A is added and stirred for 10 minutes, and degassing is performed to obtain a UV-curable polyacrylate pressure-sensitive adhesive.

[0029] Beneficial effects of the present invention:

[0030] The polyacrylate pressure-sensitive adhesive prepared by the present invention overcomes the disadvantages of poor water resistance and flame retardancy of conventional pressure-sensitive adhesives; the introduction of functional monomers can utilize organic silicon to improve the water resistance of the pressure-sensitive adhesive, and reduce the expansion and softening caused by stimulation by factors such as moisture and humidity in the external environment; the composite flame retardant enhances the flame retardancy of the matrix by combining organic and inorganic means. Therefore, the polyacrylate pressure-sensitive adhesive in the present invention has a good application prospect in the fields of automobiles, furniture manufacturing, packaging, etc.

[0031] In the functional monomer, the double bond in methyl methacrylate is first reacted with the active hydrogen in the hydrogen-containing silicone oil to generate esterified silicone oil; then the ester group in the esterified silicone oil is reacted with the amino group in the allylamine to generate a functional monomer containing a double bond structure and an organic silicon structure. The introduction of functional monomers can not only participate in the free radical polymerization reaction between acrylates, but also utilize the excellent water resistance of organic silicon to improve the water resistance of pressure-sensitive adhesives and reduce the performance degradation caused by poor water resistance.

[0032] In the composite flame retardant, imidazole and methyl acrylate are first reacted to obtain intermediate product 1; then cyanuric chloride is reacted with allylamine and ethylenediamine to generate intermediate product 2; then the amino group in intermediate product 2 is reacted with the ester group in intermediate product 1 to obtain an organic flame retardant; finally, free radical polymerization is carried out between an inorganic flame retardant containing a double bond structure and an organic flame retardant containing a double bond structure after being treated with a silane coupling agent to obtain a composite flame retardant. The introduction of composite flame retardant can significantly improve the flame retardant properties of pressure-sensitive adhesive, which is due to the synergistic effect between the triazine structure, imidazole structure and halloysite nanotubes it contains, thereby improving the flame retardant properties of the matrix; among them, the imidazole structure can promote the formation of carbon layer during combustion, play a certain flame retardant role in the condensed phase, and can also generate N-containing compounds (N2, NH3 and other non-flammable gases) with the N element in the triazine structure during combustion, thereby diluting the content of combustible gas during combustion and playing a flame retardant role in the gas phase; the introduction of halloysite nanotubes can also synergize with the flame retardant components, using its unique nanotube structure to form a barrier layer in the pressure-sensitive adhesive, which can effectively prevent the transfer of heat and oxygen, thereby slowing down the spread of flames and improving the flame retardant efficiency of the matrix. In addition, the amide structure is introduced into the composite flame retardant, and its presence can improve the adhesion of the matrix by using its strong hydrogen bonding effect. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1: The functional monomer is prepared by the following steps:

[0035] Step A1, after heating and vacuum dehydrating 0.2g of methyl methacrylate, add 5g of chloroplatinic acid isopropanol solution and 50mL of toluene, replace with nitrogen three times, add 2g of hydrogen-containing silicone oil dropwise under nitrogen conditions, heat to 80°C for reaction for 1.5h, and distill under reduced pressure to obtain esterified silicone oil. The chloroplatinic acid isopropanol solution is prepared by mixing and stirring chloroplatinic acid and isopropanol in a mass ratio of 0.05:100;

[0036] Step A2: Under nitrogen, 1 g of esterified silicone oil was mixed and stirred evenly in 100 mL of N,N-dimethylformamide, and the temperature was lowered to 0°C. Then, 0.5 g of allylamine was slowly added and stirred for 10 min. The temperature was then raised to 120°C and the reaction was carried out for 2 h. The functional monomer was obtained by rotary evaporation.

[0037] The composite flame retardant is prepared by the following steps:

[0038] Step B1, under nitrogen conditions, add 0.01 mol of imidazole to 100 mL of methanol and stir evenly, then slowly add 0.01 mol of methyl acrylate, raise the temperature to 35° C., stir and react for 3 h, to obtain intermediate 1;

[0039] Step B2, 0.01mol cyanuric chloride, 0.2g sodium hydroxide and 100mL acetone were mixed evenly, and the temperature was controlled at 0°C, and then 50mL allylamine acetone solution was slowly added, stirred for reaction for 2h, and then the temperature was raised to 40°C, and then 50mL ethylenediamine acetone solution and 4mL, 0.1mol / L sodium hydroxide solution were slowly added dropwise in sequence, stirred for reaction for 2h, and then the temperature was raised to 90°C, and 50mL ethylenediamine acetone solution and 4mL, 0.1mol / L sodium hydroxide solution were added, and stirred for reaction for 1h to obtain intermediate product 2. The allylamine acetone solution was prepared by mixing allylamine and acetone in a dosage ratio of 0.01mol:50mL, and the ethylenediamine acetone solution was prepared by mixing ethylenediamine and acetone in a dosage ratio of 0.02mol:100mL;

[0040] Step B3, under nitrogen conditions, cool the intermediate product 2 to 0°C, slowly add the intermediate product 1 and stir for 30 minutes, then heat to 130°C and react for 2 hours to obtain an organic flame retardant, wherein the molar ratio of the intermediate product 1 to the ethylenediamine in step B2 is 1:1;

[0041] Step B4, evenly dispersing 1 g of halloysite nanotubes in 50 mL of 1,4-dioxane, adding 0.05 g of KH570, heating to 80° C., stirring and reacting for 4 h, filtering, washing and drying to obtain an inorganic flame retardant;

[0042] Step B5, add 0.5g of organic flame retardant and 1g of inorganic flame retardant into 100mL of N,N-dimethylformamide and stir to mix evenly, then add 0.005g of diisopropylbenzene peroxide, heat to 45°C, stir to react for 2h, filter, wash and dry to obtain a composite flame retardant.

[0043] Example 2: Functional monomers are prepared by the following steps:

[0044] Step A1, after heating and vacuum dehydrating 0.5g of methyl methacrylate, add 7g of chloroplatinic acid isopropanol solution and 50mL of toluene, replace with nitrogen three times, add 3.5g of hydrogenated silicone oil dropwise under nitrogen conditions, heat to 85°C for reaction for 2h, and distill under reduced pressure to obtain esterified silicone oil. The chloroplatinic acid isopropanol solution is prepared by mixing and stirring chloroplatinic acid and isopropanol in a mass ratio of 0.075:100;

[0045] Step A2: Under nitrogen, 3 g of esterified silicone oil was mixed and stirred in 100 mL of N, N-dimethylformamide, and the temperature was lowered to 0°C. Then, 1 g of allylamine was slowly added and stirred for 20 min. The temperature was then raised to 130°C and the reaction was carried out for 2.5 h. The functional monomer was obtained by rotary evaporation.

[0046] The composite flame retardant is prepared by the following steps:

[0047] Step B1, under nitrogen conditions, add 0.02 mol of imidazole to 100 mL of methanol and stir evenly, then slowly add 0.02 mol of methyl acrylate, raise the temperature to 35° C., stir and react for 4 hours to obtain intermediate product 1;

[0048] Step B2, 0.015mol cyanuric chloride, 0.3g sodium hydroxide and 100mL acetone were mixed evenly, and the temperature was controlled at 2°C, and then 50mL allylamine acetone solution was slowly added, stirred and reacted for 2.5h, and then the temperature was raised to 45°C, and then 50mL ethylenediamine acetone solution and 6mL, 0.1mol / L sodium hydroxide solution were slowly added dropwise in sequence, stirred and reacted for 2.5h, and then the temperature was raised to 90°C, and 50mL ethylenediamine acetone solution and 6mL, 0.1mol / L sodium hydroxide solution were added, and stirred and reacted for 1.5h to obtain intermediate product 2, wherein the allylamine acetone solution is prepared by mixing and stirring allylamine and acetone in a dosage ratio of 0.015mol:50mL, and the ethylenediamine acetone solution is prepared by mixing and stirring ethylenediamine and acetone in a dosage ratio of 0.03mol:100mL;

[0049] Step B3, under nitrogen conditions, cool the intermediate product 2 to 0°C, slowly add the intermediate product 1 and stir for 30 minutes, then heat to 140°C and react for 2.5 hours to obtain an organic flame retardant, wherein the molar ratio of the intermediate product 1 to the ethylenediamine in step B2 is 1:1;

[0050] Step B4, 2 g of halloysite nanotubes were evenly dispersed in 50 mL of 1,4-dioxane, and 0.1 g of KH570 was added, the temperature was raised to 85° C., stirred and reacted for 5 h, filtered, washed and dried to obtain an inorganic flame retardant;

[0051] Step B5, add 1g of organic flame retardant and 1.5g of inorganic flame retardant into 100mL of N,N-dimethylformamide and stir to mix evenly, then add 0.01g of diisopropylbenzene peroxide, heat to 50°C, stir to react for 2.5h, filter, wash and dry to obtain a composite flame retardant.

[0052] Example 3: Functional monomers are prepared by the following steps:

[0053] Step A1, after heating and vacuum dehydrating 1g of methyl methacrylate, add 10g of chloroplatinic acid isopropanol solution and 50mL of toluene, replace with nitrogen three times, add 5g of hydrogenated silicone oil dropwise under nitrogen conditions, heat to 90°C for reaction for 2.5h, and distill under reduced pressure to obtain esterified silicone oil. The chloroplatinic acid isopropanol solution is prepared by mixing and stirring chloroplatinic acid and isopropanol in a mass ratio of 0.1:100;

[0054] Step A2: Under nitrogen, 5 g of esterified silicone oil was mixed and stirred evenly in 100 mL of N, N-dimethylformamide, and the temperature was lowered to 0°C. Then, 2 g of allylamine was slowly added and stirred for 30 min. The temperature was then raised to 140°C and reacted for 3 h. The functional monomer was obtained by rotary evaporation.

[0055] The composite flame retardant is prepared by the following steps:

[0056] Step B1, under nitrogen conditions, add 0.03 mol of imidazole to 100 mL of methanol and stir evenly, then slowly add 0.03 mol of methyl acrylate, raise the temperature to 35° C., stir and react for 5 hours to obtain intermediate product 1;

[0057] Step B2, 0.02mol cyanuric chloride, 0.4g sodium hydroxide and 100mL acetone were mixed evenly, and the temperature was controlled at 5°C, and then 50mL allylamine acetone solution was slowly added, stirred for reaction for 3h, and then the temperature was raised to 50°C, and then 50mL ethylenediamine acetone solution and 8mL, 0.1mol / L sodium hydroxide solution were slowly added dropwise in sequence, stirred for reaction for 3h, and then the temperature was raised to 90°C, and 50mL ethylenediamine acetone solution and 8mL, 0.1mol / L sodium hydroxide solution were added, and stirred for reaction for 2h to obtain intermediate product 2, wherein the allylamine acetone solution is prepared by mixing and stirring allylamine and acetone in a dosage ratio of 0.02mol:50mL, and the ethylenediamine acetone solution is prepared by mixing and stirring ethylenediamine and acetone in a dosage ratio of 0.04mol:100mL;

[0058] Step B3, under nitrogen conditions, cool the intermediate product 2 to 0°C, slowly add the intermediate product 1 and stir for 30 minutes, then heat to 150°C and react for 3 hours to obtain an organic flame retardant, wherein the molar ratio of the intermediate product 1 to the ethylenediamine in step B2 is 1:1;

[0059] Step B4, 3 g of halloysite nanotubes were evenly dispersed in 50 mL of 1,4-dioxane, and 0.2 g of KH570 was added, the temperature was raised to 90° C., stirred and reacted for 6 h, filtered, washed and dried to obtain an inorganic flame retardant;

[0060] Step B5, add 1.5g of organic flame retardant and 2g of inorganic flame retardant into 100mL of N,N-dimethylformamide and stir to mix evenly, then add 0.015g of diisopropylbenzene peroxide, heat to 55°C, stir to react for 3h, filter, wash and dry to obtain a composite flame retardant.

[0061] Example 4: A method for preparing a UV-curable polyacrylate pressure-sensitive adhesive comprises the following steps:

[0062] 45 parts of isooctyl acrylate, 15 parts of butyl acrylate, 8 parts of methyl methacrylate, 1 part of acrylic acid, 5 parts of the functional monomer prepared in Example 1, 5 parts of the composite flame retardant prepared in Example 1, 0.1 parts of a crosslinking agent, and 0.1 parts of a photoinitiator TPO;

[0063] Step S1, weighing raw materials by weight, mixing isooctyl acrylate, butyl acrylate, methyl methacrylate, acrylic acid, the functional monomer prepared in Example 1 and 25 wt % of the photoinitiator TPO, and irradiating with a low-pressure mercury lamp at 1 mW / cm 2 Irradiate with ultraviolet light of intensity of 200 nm for 2 min to obtain material A;

[0064] Step S2, after uniformly mixing the composite flame retardant prepared in Example 1, trimethylolpropane triacrylate and the remaining photoinitiator TPO, adding material A and stirring for 10 minutes, degassing, to obtain a UV-curable polyacrylate pressure-sensitive adhesive.

[0065] Example 5: A method for preparing a UV-curable polyacrylate pressure-sensitive adhesive comprises the following steps:

[0066] 50 parts of isooctyl acrylate, 20 parts of butyl acrylate, 12 parts of methyl methacrylate, 2 parts of acrylic acid, 7 parts of the functional monomer prepared in Example 2, 7 parts of the composite flame retardant prepared in Example 2, 0.2 parts of a crosslinking agent, and 1 part of a photoinitiator TPO;

[0067] Step S1, weighing raw materials by weight, mixing isooctyl acrylate, butyl acrylate, methyl methacrylate, acrylic acid, the functional monomer prepared in Example 2 and 25wt% of the photoinitiator TPO, and irradiating with a low-pressure mercury lamp at 3mW / cm2 under nitrogen conditions. 2 Irradiate with ultraviolet light of intensity of 300 nm for 3 min to obtain material A;

[0068] Step S2, after uniformly mixing the composite flame retardant prepared in Example 2, trimethylolpropane triacrylate and the remaining photoinitiator TPO, adding material A and stirring for 10 minutes, degassing, to obtain a UV-curable polyacrylate pressure-sensitive adhesive.

[0069] Example 6: A method for preparing a UV-curable polyacrylate pressure-sensitive adhesive comprises the following steps:

[0070] 55 parts of isooctyl acrylate, 25 parts of butyl acrylate, 15 parts of methyl methacrylate, 3 parts of acrylic acid, 9 parts of the functional monomer prepared in Example 3, 10 parts of the composite flame retardant prepared in Example 3, 0.3 parts of a crosslinking agent, and 2 parts of a photoinitiator TPO;

[0071] Step S1, weighing raw materials by weight, mixing isooctyl acrylate, butyl acrylate, methyl methacrylate, acrylic acid, the functional monomer prepared in Example 3 and 25wt% of photoinitiator TPO, and irradiating with a low-pressure mercury lamp at 5mW / cm2 under nitrogen conditions. 2 Irradiate with ultraviolet light of intensity of 4 min to obtain material A;

[0072] Step S2, after uniformly mixing the composite flame retardant prepared in Example 3, trimethylolpropane triacrylate and the remaining photoinitiator TPO, adding material A and stirring for 10 minutes, degassing, to obtain a UV-curable polyacrylate pressure-sensitive adhesive.

[0073] Comparative Example 1: This comparative example is a polyacrylate pressure-sensitive adhesive, which is different from Example 5 in that ethyl acrylate is used instead of the functional monomer prepared in Example 2, and the rest are the same.

[0074] Comparative Example 2: This comparative example is a polyacrylate pressure-sensitive adhesive. The difference from Example 5 is that dimethyl methylphosphonate is used instead of the composite flame retardant prepared in Example 2, and the rest are the same.

[0075] Performance test: The polyacrylate pressure-sensitive adhesive prepared in Examples 4-6 and Comparative Examples 1-2 was surface treated with a silicone release agent on polyethylene terephthalate (PET), and the polyacrylate pressure-sensitive adhesive was coated between two PET films after treatment, and then pressed to obtain a sheet; a low-pressure mercury lamp was used to irradiate both sides of the sheet with ultraviolet light at an intensity of 0.6 mW / cm 2 The irradiation time was 5 min, and then 7.0 mW / cm2 The strength of the adhesive tape was irradiated with ultraviolet light for 5 minutes to obtain a sheet adhesive tape with a thickness of 0.6 mm; the sheet adhesive tape was then tested for water resistance, flame retardancy and peel strength, and the test results are shown in Table 1;

[0076] Water resistance test: refer to GB / T 1733-199 standard, place the sheet adhesive tape in a culture dish, weigh the dry weight of the sheet adhesive tape and the culture dish, immerse the sheet adhesive tape in water, take it out, absorb the surface moisture with filter paper, weigh the wet film weight, and calculate the water absorption rate;

[0077] Flame retardant performance test: Test the flame retardant grade of the rubber strip on a horizontal and vertical combustion apparatus according to UL94-2006 standard;

[0078] Peel strength test: The 180° peel strength of the rubber strip is tested on an electronic tensile testing machine in accordance with GB / T 2792-2014 standard.

[0079] Table 1: Performance test results

[0080] Water absorption (%) Flame retardant grade Peel strength (N / 25mm) Example 4 5.53 V-0 9.86 Example 5 5.26 V-0 10.11 Example 6 5.42 V-0 10.03 Comparative Example 1 10.63 V-0 8.91 Comparative Example 2 6.16 V-2 9.02

[0081] As can be seen from Table 1, the polyacrylate pressure-sensitive adhesive prepared by the present invention has a lower water absorption rate after the water absorption test, indicating that it has excellent water resistance; after the flame retardant performance test, the flame retardant grade is V-0, indicating that it has excellent flame retardant performance; after the peel strength test, the peel strength is in the range of (9.86-10.11) N / 25mm, indicating that it has excellent adhesion.

[0082] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A UV-curable polyacrylate pressure-sensitive adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 45-55 parts of isooctyl acrylate, 15-25 parts of butyl acrylate, 8-15 parts of methyl methacrylate, 1-3 parts of acrylic acid, 5-9 parts of functional monomer, 5-10 parts of composite flame retardant, 0.1-0.3 parts of crosslinking agent and 0.1-2 parts of photoinitiator; The photoinitiator is photoinitiator TPO, and the crosslinking agent is trimethylolpropane triacrylate; The functional monomer is prepared by the following steps: Step A1, after heating and vacuum dehydrating methyl methacrylate, add chloroplatinic acid isopropanol solution and toluene, replace with nitrogen three times, add hydrogenated silicone oil dropwise under nitrogen, heat to 80-90°C for reaction for 1.5-2.5h, and distill under reduced pressure to obtain esterified silicone oil; Step A2: Under nitrogen, mix the esterified silicone oil in N,N-dimethylformamide and stir evenly, cool to 0°C, then slowly add allylamine and stir for 10-30 minutes, then heat to 120-140°C and react for 2-3 hours, and rotary evaporate to obtain the functional monomer.

2. A UV curable polyacrylate pressure sensitive adhesive according to claim 1, characterized in that: In step A1, the usage ratio of methyl methacrylate, chloroplatinic acid isopropanol solution, toluene and hydrogen-containing silicone oil is 0.2-1g:5-10g:50mL:2-5g, and the chloroplatinic acid isopropanol solution is prepared by mixing and stirring chloroplatinic acid and isopropanol in a mass ratio of 0.05-0.1:

100.

3. A UV curable polyacrylate pressure sensitive adhesive according to claim 1, characterized in that: In step A2, the usage ratio of esterified silicone oil, N,N-dimethylformamide and allylamine is 1-5g:100mL:0.5-2g.

4. The UV curable polyacrylate pressure sensitive adhesive according to claim 1, characterized in that: The composite flame retardant is prepared by the following steps: Step B1, under nitrogen conditions, imidazole was added to methanol and mixed and stirred evenly, and then methyl acrylate was slowly added, and the temperature was raised to 35° C. and stirred for reaction for 3-5 hours to obtain intermediate product 1; Step B2, mix cyanuric chloride, sodium hydroxide and acetone evenly, control the temperature at 0-5°C, slowly add allylamine acetone solution, stir and react for 2-3h, then heat to 40-50°C, slowly drop half volume of ethylenediamine acetone solution and half volume of 0.1mol / L sodium hydroxide solution in sequence, stir and react for 2-3h, then heat to 90°C, add the remaining volume of ethylenediamine acetone solution and the remaining volume of 0.1mol / L sodium hydroxide solution, stir and react for 1-2h, and obtain intermediate product 2; Step B3, under nitrogen conditions, cool the intermediate product 2 to 0°C, slowly add the intermediate product 1 and stir for 30 minutes, then heat to 130-150°C and react for 2-3 hours to obtain an organic flame retardant; Step B4, uniformly dispersing the halloysite nanotubes in 1,4-dioxane, adding KH570, heating to 80-90° C., stirring and reacting for 4-6 hours, filtering, washing and drying to obtain an inorganic flame retardant; Step B5, adding the organic flame retardant and the inorganic flame retardant to N,N-dimethylformamide and stirring to mix evenly, then adding diisopropylbenzene peroxide, heating to 45-55° C., stirring to react for 2-3 hours, filtering, washing and drying to obtain a composite flame retardant.

5. A UV curable polyacrylate pressure sensitive adhesive according to claim 4, characterized in that: In step B1, the usage ratio of imidazole, methanol and methyl acrylate is 0.01-0.03 mol:100 mL:0.01-0.03 mol.

6. A UV curable polyacrylate pressure sensitive adhesive according to claim 4, characterized in that: In step B2, the dosage ratio of cyanuric chloride, sodium hydroxide, acetone, allylamine acetone solution, ethylenediamine acetone solution and sodium hydroxide solution is 0.01-0.02 mol: 0.2-0.4 g: 100 mL: 50 mL: 100 mL: 8-16 mL, the allylamine acetone solution is prepared by mixing allylamine and acetone in a dosage ratio of 0.01-0.02 mol: 50 mL, and the ethylenediamine acetone solution is prepared by mixing ethylenediamine and acetone in a dosage ratio of 0.02-0.04 mol: 100 mL.

7. A UV curable polyacrylate pressure sensitive adhesive according to claim 4, characterized in that: The molar ratio of the intermediate product 1 in step B3 to the ethylenediamine in step B2 is 1:

1.

8. The UV curable polyacrylate pressure sensitive adhesive according to claim 4, characterized in that: In step B4, the usage ratio of halloysite nanotubes, 1,4-dioxane and KH570 is 1-3 g:50 mL:0.05-0.2 g.

9. The UV curable polyacrylate pressure sensitive adhesive according to claim 4, characterized in that: In step B5, the usage ratio of the organic flame retardant, the inorganic flame retardant, N,N-dimethylformamide and dicumyl peroxide is 0.5-1.5 g: 1-2 g: 100 mL: 0.005-0.015 g.

10. A method for preparing the UV-curable polyacrylate pressure-sensitive adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1, weigh the raw materials by weight, mix isooctyl acrylate, butyl acrylate, methyl methacrylate, acrylic acid, functional monomers and part of the photoinitiator, and illuminate the mixture with a low-pressure mercury lamp at 1-5 mW / cm2 under nitrogen conditions. 2 Irradiate with ultraviolet light of intensity of 2-4min to obtain material A; Step S2: after the composite flame retardant, the crosslinking agent and the remaining amount of the photoinitiator are uniformly mixed, material A is added and stirred for 10 minutes, and degassing is performed to obtain a UV-curable polyacrylate pressure-sensitive adhesive.